Non-Menkes Type Copper Deficiency - J Gordon Millichap (Pediatric Neurology Briefs Publishers, 1991)
A two year old girl with copper deficiency progressive neuronal disorder and granulocytopenia is reported from the Department of Pediatrics, Kyoto University, Japan.